Preliminary Study of the Use of Online Games Between University Students with and without Disabilities - Suriá Martínez, Raquel; Villegas Castrillo, Esther; López Sánchez, Carmen; Carretón Ballester, Carmen; García-Castillo, Fernando (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This research is part of a project granted by the Ministry of Consumer Affairs (2023) and is aimed at knowing the degree of use, abuse or addiction that the population of university students at the University of Alicante with and without disabilities has, as well as exploring the perception of their risk behaviors in gambling and online betting. 370 students collaborated by completing a questionnaire. The results indicated that the students do not play very frequently, with a greater gaming habit observed in the group with disabilities. It would be interesting if the university offered counseling and support designed to prevent gambling problems.